Microbial communities on dry natural rocks are richer and less stressed than those on man-made playgrounds - Manninen, Juulia; Saarenpää, Mika; Roslund, Marja; Galitskaya, P.; Sinkkonen, Aki (American Society for Microbiology, 2025)
In modern urbanized societies, the incidence of major immune-mediated diseases is several times higher than before World War II. A potential explanation is that these diseases are triggered by limited possibilities to be exposed to rich environmental microbiota. This requires that the urban environment hosts less and poorer microbiota than the natural environment. The current study was designed to test the assumption that urban man-made environments host less and poorer environmental microbiota, compared to natural habitats. We selected two types of dry environments, natural rocks and playground rubber mats, both of which were used daily and extensively by children. In quantitative PCR and next-generation sequencing, bacterial abundance and richness were higher on the natural rocks than the rubber mats. Altogether, 67 amplicon sequence variants (ASVs) belonging mostly to Actinobacteria and Proteobacteria were indicative of rock microbiota, while three ASVs were indicative of rubber mats. Interestingly, bacteria formed more complex networks on rubber mats than natural rocks. Based on the literature, this indicates that the studied artificial dry environment is more challenging and stressful for bacterial communities than dry natural rocks. The results support the hypothesis that urban man-made environments host poor microbial communities, which is in accordance with the biodiversity hypothesis of immune-mediated diseases.
Keywords: biodiversity hypothesis; urban environment; microbial communitycomposition; soil microbiota; urban microbiome; planetary health; microbial exposure; play environments